The Influence of Physical Activity on Quality of Life and Anxiety among University Students - Husni Mubarak; Mustika Fitri; Komarudin (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aimed to examine the influence of physical activity on quality of life and anxiety among university students involved in sports communities. The researcher also highlights the potential role of social support particularly from close individuals in enhancing student-athletes motivation. The subjects of this study were 65 students who participated in sports communities, selected using probability sampling through proportionate stratified random sampling. A quantitative research approach was employed, utilizing the third type of causal-comparative research, namely consequence exploration. The hypothesis was tested using bootstrapped regression analysis through SPSS version 27. The results showed that physical activity did not have a significant effect on any of the four dimensions of students’ quality of life: physical (p = 0.243), psychological (p = 0.155), social (p = 0.352), and environmental (p = 0.137). Additionally, physical activity did not show a significant effect on anxiety levels (p = 0.137). Since all significance values were greater than 0.05, the findings indicate that physical activity does not have a statistically significant influence on quality of life or anxiety among university students.